Reflecting on Iban women's studies - Jawan, Jayum (Tun Jugah Foundation, 2021)
This paper attempts to briefly discuss the state of studies on Iban women of Sarawak, Malaysia. What aspects have been studies about Iban women? This review aims to have a perspective on the subject and suggest ways to move forward. Some of the issues addressed in this paper are as follow: the position of ]ban women in their society based on Adat and actual practices; how ]ban women's position in their society has changed over time and in which direction; and what are the pressing issues facing ]ban women today. In the above attempt, the paper will also briefly: discuss what important studies have been undertaken on various aspects of]· ban women. The paper will conclude with a brief introduction to the Tan Sri Empiang Jabu Research Chair on Dayak Womens' Studies and how this academic initiative between Universiti Putra Malaysia (UPM) and Sarakup Indu Dayak Sarawak (SIDS) plans to assist in better understanding issues and challenges facing Dayak women and therefore connect these research initiatives to policy-making for the betterment of Dayak and especially ]ban women.